Interleukin‐4 and interleukin‐13 evoke scratching behaviour in mice. Issue 12 (1st October 2019) - Campion, Michelle; Smith, Leila; Gatault, Solène; Métais, Charles; Buddenkotte, Jörg; Steinhoff, Martin
Abstract: Persistent and relapsing itch commonly manifests in inflammatory skin disorders such as atopic dermatitis (AD). AD pathogenesis is driven by interleukin‐4 (IL‐4) and interleukin‐13 (IL‐13). Dupilumab, a monoclonal antibody blocking the action of IL‐4 and IL‐13 effectively reduces the symptoms of AD and itch. Little is known whether IL‐4 and IL‐13 directly contribute to itch transduction. A recently published study (Oetjen et al, Cell, 2017, 171, 217) found IL‐4 and IL‐13 to directly activate itch‐sensory neurons in vitro. Surprisingly, they found no significant increase in scratching after intradermally injecting high doses (2.5 ug/ml) of IL‐4 and IL‐13 into mice. Similar experiments in our lab, however, suggested that both IL‐4 and IL‐13 contribute to acute itch in vivo. We intradermally injected lower doses (1 ug/ml) of IL‐4 and IL‐13 into mice and found a significant increase of scratching bouts compared to vehicle. Interestingly, the combined treatment of IL‐4 and IL‐13 produced additive increase of scratching and acute pruritus at an earlier time point compared to each cytokine administered alone. In summary, our study shows a rapid and significant increase of scratching after intradermal injection of IL‐4, IL‐13 or combined IL‐4/ IL‐13 compared to vehicle in mice 5‐10 minutes after injection. Our data suggest that IL‐4 and IL‐13 alone and combined directly act as potent acute pruritogens on sensory nerves. This finding expands our understanding of cytokines as pruritogens, how targeted anticytokine medications act in AD, and about neuroimmune communication in the skin.